Communication of a mental health diagnosis: a systematic synthesis and narrative review - Milton, A.; Mullan, Barbara (Informa Healthcare, 2014)
Background: There is limited understanding of the mechanisms used to effectively communicate with service-users about their mental health diagnoses. Aims: To conduct a systematic synthesis of studies that present data on the communication of a psychiatric diagnosis. Methods: Comprehensive database and manual searches were conducted resulting in the inclusion of 30 quantitative and qualitative papers. Results: The majority of studies were descriptive. The rate of service-users being informed of their diagnosis has increased over the past decade. Consumer communication preferences were not always satisfactorily addressed in practice. Individual characteristics of service-users and clinicians influenced whether a diagnostic discussion took place. Results from intervention studies aimed at facilitating diagnostic communication reported significant improvements in service-user satisfaction and mood and clinician communication skills. Conclusions: This review highlights a gap in the system of communication between clinicians and service-users. To assist clinicians to talk effectively with individuals about their mental health, communication protocols and training need to be further developed and assessed. Such developments would benefit from well-designed randomised controlled trial protocols, should incorporate service-users’ preferences and address stigma-related concerns.